Hotel business development strategy in the conditions of war (Economics and region, 2023)
The hostilities had a negative impact on the hotel market, so companies are forced to look for new ways of survival and functioning, to develop effective development strategies. The article examines the essence of the company's strategy, the stages of its formation, as well as types of strategies. It was found that the accommodation facilities of the central, southern and eastern parts of Ukraine were the most affected by the hostilities. It was established that as a result of hostilities, receipts to the state budget from the tourism industry in the first six months of 2022 decreased by almost 26% compared to the same period in 2021. The largest share of revenues to the state budget was paid by hotels and sanatoriums, contributions from boarding houses and dormitories, which were used as a shelter for temporarily displaced persons, increased. The largest amount of taxes paid for the first half of 2022 was demonstrated by the city of Kyiv and the Lviv, Ivano-Frankivsk, Kyiv, and Odesa regions. It was investigated that in the first six months of 2022, 28% more tourist tax was paid compared to the same period in 2021. The city of Kyiv, Lviv, Zakarpattia, Ternopil, and Khmelnytskyi regions were the leaders in paying the tourist tax. Various hotel business development strategies that can be applied in order to survive the war are identified: security improvement, repurposing, innovation, creating a good website, Digital marketing, reviewing the supplier base, personnel management strategies, social responsibility, implementing sustainable hotel practices, emphasis on mobile-friendly services, contactless services, cost-benefit analysis.
Keywords: strategy; hotel business; tourist tax; innovation; digital marketing